Antidepressant therapies inhibit inflammation and microglial M1-polarization - Kalkman, Hans O.; Feuerbach, Dominik (Pharmacology & therapeutics (Oxford), 2016)
Macrophages and their counterparts in the central nervous system, the microglia, detect and subsequently clear microbial pathogens and injured tissue. These phagocytic cells alter and adapt their phenotype depending on their prime activity, i.e., whether they participate in acute defence against pathogenic organisms ('M1'-phenotype) or in clearing damaged tissues and performing repair activities ('M2'-phenotype). Stimulation of pattern recognition receptors by viruses (vaccines), bacterial membrane components (e.g., LPS), alcohol, or long-chain saturated fatty acids promotes M1-polarization. Vaccine or LPS administration to healthy human subjects can result in sickness symptoms and low mood. Alcohol abuse and abdominal obesity are recognized as risk factors for depression. In the M1-polarized form, microglia and macrophages generate reactive oxygen and nitrogen radicals to eradicate microbial pathogens. Inadvertently, also tetrahydrobiopterin (BH4) may become oxidized. This is an irreversible reaction that generates neopterin, a recognized biomarker for depression. BH4 is a critical cofactor for the synthesis of dopamine, noradrenaline, and serotonin, and its loss could explain some of the symptoms of depression. Based on these aspects, the suppression of M1-polarization would limit the inadvertent catabolism of BH4. In the current review, we evaluate the evidence that antidepressant treatments (monoamine reuptake inhibitors, PDE4 inhibitors, lithium, valproate, agomelatine, tianeptine, electroconvulsive shock, and vagus nerve stimulation) inhibit LPS-induced microglia/macrophage M1-polarization. Consequently, we propose that supplementation with BH4 could limit the reduction in central monoamine synthesis and might represent an effective treatment for depressed mood.